2005
DOI: 10.1590/s1516-89132005000200009
|View full text |Cite
|
Sign up to set email alerts
|

Selenium protective activity against aflatoxin B1 adverse affects on Drosophila melanogaster

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
6
0
3
Order By: Relevance
“…It is generally accepted that this element is a crucial component of several vital metabolic pathways, the antioxidant defense system and the functioning of the immune system [ 51 ]. A growing number of evidence revealed that Se has emerged as an important element in the dietary prevention of various toxic agents [ 52 , 53 ]. Se could inhibit gross and histopathological lesions in most of the organs induced by AFB 1 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that this element is a crucial component of several vital metabolic pathways, the antioxidant defense system and the functioning of the immune system [ 51 ]. A growing number of evidence revealed that Se has emerged as an important element in the dietary prevention of various toxic agents [ 52 , 53 ]. Se could inhibit gross and histopathological lesions in most of the organs induced by AFB 1 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selenium might enhance the conjugation of aflatoxins by increasing excretion of the aflatoxins and by preventing the formation of AFB1-DNA adducts. The protective effect of selenium is mediated through a cellular mechanism related to glutathione detoxification pathways [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Em vários carcinomas, principalmente o hepático, é característico este tipo de alteração (PINHEIRO, 2004, FERREIRA et al, 2006. (CALONI et al, 2006;UYSAL et al, 2005;MASSEY et al, 1995;McLEAN;DUTTON, 1995;FORRESTER et al, 1990).…”
Section: Aflatoxinasunclassified
“…Todavia, os padrões de biotransformação da AFB 1 possuem uma variação muito grande inter ou intra-espécie, o que explicaria os diferentes graus de suscetibilidade à AFB 1 (UYSAL et al, 2005;LOPES et al, 2005;BUSBY;WOGAN, 1984).…”
Section: Aflatoxinasunclassified
See 1 more Smart Citation